Heterologous cross-expression of oxygenase and glycosyltransferase genes in streptomycetes, producing angucyclic antibiotics - Kobylyanskyy, A.; Ostash, B.; Fedorenko V. (Цитология и генетика, 2009)
The heterologous expression of oxygenase genes urdM, ovmOIII, lanM2, lndZ5 and glycosyltransferase gene urdGT2 in different angucycline producers of genus Streptomyces has been carried out. The introduction of genes urdM, lanM2 and urdGT2 results in the accumulation of new glycosylated compounds in several strains under investigation. A number of processed recombinant strains display streptomycin sensitivity and decrease in total antibacterial activity. The obtained data is an evidence of changes in antibiotics production, resulting from post polyketide synthase (postPKS) tailoring gene expression across streptomycete strains. Our study demonstrates the potential of post PKS tailoring genes for generation of novel bioactive metabolites. Здійснено гетерологічну експресію генів оксигеназ urdM, ovmOIII, lanM2, lndZ5 та глікозилтрансферази urdGT2 у різних видів продуцентів ангуциклінів з роду Streptomyces. Введення генів urdM, lanM2 та urdGT2 у деякі з досліджуваних штамів зумовлює накопичення ними нових глікозильованих сполук. Виявлено виникнення чутливості до стрептоміцину та різке зниження загальної антибактерійної активності у деяких із одержаних рекомбінантних штамів. Отримані дані є свідченням модифікації продукції антибіотиків, яка є наслідком експресії генів постполікетидного синтезу (пост-ПКС) у штамах стрептоміцетів. Наші дослідження демонструють потенціал генів пост-ПКС у створенні нових біологічно активних метаболітів. Проведена гетерологическая экспрессия генов оксигеназ urdM, ovmOIII, lanM2, lndZ5 и гликозилтрансферазы urdGT2 в разных видах продуцентов ангуциклинов из рода Streptomyces. Введение генов urdM, lanM2 и urdGT2 в некоторые из исследуемых штаммов обусловливает накопление ими новых гликозилированных соединений. Обнаружено появление чувствительности к стрептомицину и резкое снижение общей антибактериальной активности у некоторых из полученных рекомбинантных штаммов. Представленные данные свидетельствуют о модификации продукции антибиотиков, которая является следствием экспрессии генов пост-поликетидного синтеза (пост-ПКС) в штаммах стрептомицетов. Наши исследования демонстрируют потенциал генов пост-ПКС в создании новых биологически активных метаболитов.